Biological and Physico-Chemical Properties of Composite Layers Based on Magnesium-Doped Hydroxyapatite in Chitosan Matrix - Simona Liliana Iconaru; Carmen Steluta Ciobanu; Gabriel Predoi; Krzysztof Rokosz; Mariana Carmen Chifiriuc; Coralia Bleotu; George Stanciu; Radu Hristu; Steinar Raaen; Stefania Mariana Raita; Liliana Ghegoiu; Monica Luminita Badea; et al. (Micromachines, 2022)
In the present study, we report the development and characterization of composite layers (by spin coating) based on magnesium-doped hydroxyapatite in a chitosan matrix, (Ca10−xMgx(PO4)6(OH)2; xMg = 0, 0.08 and 0.3; HApCh, 8MgHApCh and 30MgHApCh). The MgHApCh composite layers were investigated using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and X-ray photoelectron spectroscopy (XPS) techniques. The in vitro biological evaluation included the assessment of their cytotoxicity on MG63 osteoblast-like cells and antifungal activity against Candida albicans ATCC 10231 fungal cell lines. The results of the physico-chemical characterization highlighted the obtaining of uniform and homogeneous composite layers. In addition, the biological assays demonstrated that the increase in the magnesium concentration in the samples enhanced the antifungal effect but also decreased their cytocompatibility. However, for certain optimal magnesium ion concentrations, the composite layers presented both excellent biocompatibility and antifungal properties, suggesting their promising potential for biomedical applications in both implantology and dentistry.